TURKISH IMAGE IN THE WEST DURING THE OTTOMAN EMPIRE: HISTORICAL FACTS AND PRESENT DAY CONNOTATIONS - Evler, Ali; Toplu, Mehmet (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Throughout history there have been opposing forces, one of which is the conflict between ‘West and East’ as Huntington claims. One of the earliest, major competitions, in this matter, has been the one with Ottoman Empire, representing Islam and European countries, followers of Christianity. These forces have been clashing in the form of several means and for reasons to predominate each other if they can achieve it at all. How has such a ‘clash’ begun between civilizations and what is the present status of it between Turkey and Western countries? This study aims at highlighting the background from a historical point of view beginning with the capture of Jerusalem by Ottoman Turks and how Turkish Image is created and portrayed in Early English Plays in relation to the rise and fall of Ottoman Empire as depicted in The Sultan Speaks by Linda McJannet. Since the core of the Ottoman Empire is modern Turkey today, the recent changes in their image on the way to full membership to the EU as well as to ‘interreligious/intercultural dialog’ in an attempt to bring peace to both parties in question for a sustainable and amicable future. It is concluded that there are still concerns between the global signatories. It will take some more time and effort to mature the thinking that they could live harmoniously developing their countries economically and their democracies for a mutual understanding. Key Words: Turkish Image, Early Modern Plays, Ottoman Empire, Islam, Turks.